The Inflationary Process in Open Economies - Martin F.J. Prachowny (Queen's University, Department of Economics, 1971)
While the concept of "imported inflation" and its relevance for open economies have received considerable attention in the policy-oriented literature, the theoretical underpinnings of this phenomenon have not been constructed as carefully as might be desirable in view of the controversial nature of the subject. The inflationary process can be transmitted to a country by developments in international capital and money markets or through the interaction of goods markets in one country with those of the rest of the world. The debate concerning the former transmission mechanism involves the difficulties in dichotomizing the balance of payments and the domestic money supply through the sterilization of foreign exchange gains or losses. In this paper, major emphasis will be given to the transmission of the inflationary process through the goods and services markets. Primarily,we are interested in investigating the determinants of the rate of inflation for a small country which, because of its size, is forced to accept certain conditions imposed by the external environment.
Keywords: 330